SHIRIDHANYA MILLETS IN INDIAN LITERATURE AND THEIR RELEVANCE TO SUSTAINABLE NUTRITION SCIENCE - Khan, Aaysha Tahera (International Journal of Research -GRANTHAALAYAH, 2026)
In India, the traditional concept of food is related to the basis of health, moral life, and economic goodwill rather than a biological need. Ved, Ayurveda, Puran and traditional folk, all Indian traditional literature, mention millets such as barley, foxtail millets, barnyard millets, and finger millet. These grains were precious for their unique qualities, such as a good nutritional profile, being environmentally friendly and their support in maintaining population health in adverse conditions. The term shiridhanya is used in the context of traditional Indian agriculture as a specific category of grains that are nutrition-rich and good for health. The word shiridhanya is a Sanskrit word made up of the word shiri and dhanya, where “shiri” means prosperity/wealth and “dhanya” means grain. These grains were precious for their unique qualities, such as a good nutritional profile, being environmentally friendly and their support in maintaining population health in adverse conditions. In the present scenario, worldwide issues related to altered climate, drop in dietary diversity, micronutrient deficiency as well as lifestyle-related disease has revealed the importance and significance of traditional food. Nutrition science continuously focuses on millets as climate tolerant crops, nutritional rich such as: high fiber, high micronutrients and bioactive compounds as well as their fewer utilization of natural resources than dominant serial crops. The present paper focuses on millets as traditional Indian food and their contemporary relation to modern nutrition science.